Nuclear energy, human capital, and urbanization tackling environmental concerns in India: evidence from QARDL and quantile co-integration - Awan A.; Kocoglu M.; Tunc A.; Tiwari A.K.; Yusoff N.Y.B.M. (Springer Science and Business Media B.V., 2025)
Besides being a nuclear power and home to 1.4 billion people, India is transforming through rapid urbanization. Given the contribution of urbanization to the improvement of living standards and economic growth, countries are pursuing it; however, policymakers are concerned about its impact on the environment. Against this backdrop, this study analyzed the influence of urbanization and nuclear energy on ecological footprints while also considering economic growth and natural resources. To this end, the study employed annual data from 1971 to 2017. The research used the innovative QARDL approach for a thorough examination of quantile dynamics to guide policymakers. Results revealed economic growth upsurges environmental degradation while human capital and urbanization reduce ecological footprints in India. Interestingly, nuclear energy is found to have a negative impact; however, it is significant at quantiles closer to the median. Furthermore, natural resources are found to be insignificant across all quantiles. The policy implications emphasize the importance of urbanization in achieving India's sustainable environmental goals and long-run equilibrium. ? The Author(s), under exclusive licence to Springer Nature B.V. 2024.